The Technology of Didactic Materials Designing in the Process of Managing of Students Independent Work in Reliance on their Individual-typological Peculiarities - Belokoz, Elena (Pedagogika, 2015)
Contemporary society need specialists who can independently refill their knowledge, be mobile and open to innovations. That is why there is a need to strategically put to the first place such process of teaching in the higher educational institutions in which management of independent students work would promote development of socially-valuable specialist, provide development of his individuality. In order to solve presented tasks, we offer the technology of projecting didactic materials in the process of managing independent work. That work suggests diagnosis of individual-typological features of students and development of students typology; correlation of contents and structure of individual work with individual-typological features of students, balance of tasks of different complexity level. In the core of the technology is projecting and realization of phased technique of managing independent students work based on identified individual types. Research goal – to theoretically justify technology of projecting didactic materials in the process of managing independent work that is based on the individual-typological features of the students. Research methods: theoretic-methodological analysis of the scientific psychological pedagogical literature on the research problem, analysis of the results of analysis individual typological features of the student, modeling.